2019
DOI: 10.7717/peerj.8149
|View full text |Cite
|
Sign up to set email alerts
|

Simulating more realistic predation threat using attack playbacks

Abstract: Use of virtual proxies of live animals are rapidly gaining ground in studies of animal behaviour. Such proxies help to reduce the number of live experimental animals needed to stimulate the behaviour of experimental individuals and to increase standardisation. However, using too simplistic proxies may fail to induce a desired effect and/or lead to quick habituation. For instance, in a predation context, prey often employ multimodal cues to detect predators or use specific aspects of predator behaviour to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
(82 reference statements)
1
0
0
Order By: Relevance
“…Previous work showed that a blank aquarium is indeed an appropriate control in this species (48,79). N. pulcher can distinguish different species of animated fish pictures [they show a stronger response to predators and conspecifics than to herbivorous fish (48,80)], and they also can distinguish pictures and videos of fish from displays of a moving object or a nonmoving background (48,79) while showing equally low responses to a moving object and a nonmoving background (as presented in our study). This indicates that a nonmoving background is an appropriate control, as N. pulcher can distinguish moving predators from other moving objects.…”
Section: Methodssupporting
confidence: 64%
“…Previous work showed that a blank aquarium is indeed an appropriate control in this species (48,79). N. pulcher can distinguish different species of animated fish pictures [they show a stronger response to predators and conspecifics than to herbivorous fish (48,80)], and they also can distinguish pictures and videos of fish from displays of a moving object or a nonmoving background (48,79) while showing equally low responses to a moving object and a nonmoving background (as presented in our study). This indicates that a nonmoving background is an appropriate control, as N. pulcher can distinguish moving predators from other moving objects.…”
Section: Methodssupporting
confidence: 64%